Medium voltage DC system architectures - Grainger, Brandon; De Doncker, Rik W. (Institution of Engineering & Technology, 2022)
A concise and hands-on overview of medium voltage direct current (MVDC) technology for electric power grids, written by international experts with broad experience. The book covers fundamentals, converters, transformers and control for both stationary and mobile applications.
Keywords: Electric power distribution -- Direct current.; elektronické knihy; electronic books